Numerical Investigation of Blast Furnace Operation with Scrap Charging - Zhu Liu; Zi Yu; Xuefeng She; Huiqing Tang; Qingguo Xue (Metals, 2020)
One approach to reduce CO2 emission in the steelmaking industry is to recycle scrap to the blast furnace/basic oxygen furnace (BF/BOF) production system. This paper performed a numerical investigation on the BF operation with scrap charging. The investigated BF was with an inner volume of 820 m3, producing 2950 tons of hot metal per day (tHM/d). The simulated results indicated the following: Extra scrap addition in BF causes the decrease of shaft temperature, the decrease of local gas utilization, and the lowering of cohesive zone position, leading to an unstable BF running. The partial replacement of sinter with scrap in BF can mitigate the negative effects induced by scrap charging. The optimal scrap rate in the BF is 178 kg/tHM, under which the BF reaches a productivity of 3310 tHM/d, a top-gas utilization of 48.5%, and a top-gas temperature of 445 K. Compared to the base case, in the BF operation with scrap charging, the BF productivity is increased by 360 kg/tHM, its pulverized-coal rate and coke rate are decreased by 16.3 kg/tHM and 39.8 kg/tHM, respectively.